2012
DOI: 10.1002/ange.201200210
|View full text |Cite
|
Sign up to set email alerts
|

Redox‐Active Metal‐Centered Oxalato Phosphate Open Framework Cathode Materials for Lithium Ion Batteries

Abstract: Discovering revolutionary cathode materials for lithium ion batteries (LIBs) with a high power/energy density to confront the existing energy, economic, and ecologic crises is one of the persistent challenges in materials research. [1] The most promising olivine phosphate LiMPO 4 electrode materials (M = Fe, Mn, or Co) [2] have already attained maximum capacity through the development of new synthetic methods, such as downsizing, [3] conductive wiring, [3b, 4] and doping. [5] Recently, hierarchical olivine-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 53 publications
1
28
1
Order By: Relevance
“…Galvanostatic cycling using Bitrode battery tester (USA) was done to evaluate the performance of the battery via. charge-discharge cycling at ambient temperature, with further details given in [28][29][30].…”
Section: Methodsmentioning
confidence: 99%
“…Galvanostatic cycling using Bitrode battery tester (USA) was done to evaluate the performance of the battery via. charge-discharge cycling at ambient temperature, with further details given in [28][29][30].…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, the connectivity of the clusters diminish from twelve in the originalf rameworks 1-3 down to eleven for the 1@KOH and 3@KOH systemsa nd ten for the 2@KOH material, as can be deduced from the elemental analysis and the increased accessibility to the porous structure as concluded from N 2 adsorption (see detailsi nr eference [12]). All theses tructural modificationsw ere expected to have ap ositive impacto nt he ionm obility of the hydroxide ions, as ac onsequence of the higher porosity of the materials and increased basicity and hydrophilicity (see below) of the [Ni 8 (OH) 5 (EtO)] 10 + clusters after the treatment with KOH/EtOH. In this regard, since the measurement of the ion conductivity of these materials is carried out in the form of pressed pellets, we carried out as tudy on the effect of the mechanical stress on the structure of these materials by pressing them up to 0.2 GPa.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…[10] Moreover,t he effect of the deliberate introduction of defects as am eanst ob oost the ionic conductivity of MOFs hasonly been poorly studied. [11] The current report is focused on the study of ionic-conductivity characterization of the previously reported face-centered cubic (fcu)[ Ni 8 (OH) 4 (H 2 O) 2 (BDP_X) 6 ]( H 2 BDP_X = 1,4-bis(pyrazol-4-yl)benzene-4-X with X = H( 1), OH (2), NH 2 (3)) MOFs and their related modified materials K[Ni 8 (OH) 5 (EtO)(BDP_X) 5.5 ] (1@KOH, 3@KOH)a nd K 3 [Ni 8 (OH) 3 (EtO)(BDP_O) 5 ]( 2@KOH), which contain missing-linker defects, obtained after ap ost-synthetic treatment with solutions of KOH in ethanol (Figure 1). These modified materials have already been proven by us to boost carbon-capture properties as ac onsequence of their enhanced pore accessibility as ar esult of their missing-linker defect nature and increased basicity of the deprotonated [Ni 8 (OH) 5 (EtO)] 10 + clusters (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations